Pengaruh Gaji Dan Insentif Terhadap Produktivitas Kerja Karyawan Divisi Promotor CV. Lentera Galuh R Tasikmalaya - Neng Rindiani Sudrajat; Arga Sutrisna; Barin Barlian (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The aim of this research is to analyze the simultaneous significant influence of salary and incentives on employee work productivity in the Promotions Division of CV. Lentera Galuh R Tasikmalaya. Salary has a significant partial influence on employee work productivity in the Promotions Division of CV. Lentera Galuh R Tasikmalaya, while Incentives also have a significant partial influence on employee work productivity in the same division. The research method used in this study is a quantitative method with a causal associative analysis approach. The research sample consists of 39 employees of CV. Lentera Galuh R Tasikmalaya. Data were collected through questionnaires distributed to employees in the division. The analytical tool used in this research is multiple regression analysis conducted using SPSS 25.0. The research results indicate that Salary has a classification of Very Strong, Incentives have a classification of Very Strong, while Employee Work Productivity also has a Very Strong classification. The findings of this study are expected to provide a better understanding of the influence of salary and incentives on employee work productivity in CV. Lentera Galuh R Tasikmalaya and offer recommendations to the management for enhancing employee performance and productivity.